Investigation of the determinants of thermal stability of the nitrile hydratase from Geobacillus pallidus RAPc8 - Kianja, John Maina (Division of Medical Biochemistry and Structural Biology, 2017)
The mechanisms of thermal stability have been a long studied subject for many years with the aim of enhancing thermal stability of protein molecules to enhance their application in industry. The nitrile hydratases group of enzymes catalyse the hydrolysis of nitriles to amides using an exothermic catalytic mechanism. Understanding and applying specific amino acid residue mutations at specific regions in protein structures has been important for engineering of thermal stability into these often tetrameric thermolabile nitrile hydratases currently used in industry globally. At the near atomic level, the interatomic interaction(s) between specific amino acid residues governs the structure and function of nitrile hydratases. This study investigated several possible interactions responsible for conferring thermal stability to several thermostability-enhanced nitrile hydratase composite mutants generated from the wild type Geobacillus pallidus RAPc8 nitrile hydratase (NHase), namely: L103S+Y127N+F36L+D4G, M43K+T150A+S169R and D96E+D167V+M188V each labelled as 9E, 9C and 8C respectively. The composite mutants were previously developed using error-prone PCR of the wild type nitrile hydratase genes coding for the alpha and beta subunits from Geobacillus pallidus RAPc8. These composite mutants presented an opportunity to understand intramolecular thermostabilising mechanisms in this nitrile hydratase. Each individual mutation found in the composite mutants, was separately introduced into the DNA coding for the Geobacillus pallidus RAPc8 NHase by site directed mutagenesis. These individual mutants were over-expressed from E. coli and purified for further study. Using activity assays and protein melting curves, their individual thermal stability contributions were determined and represented as the difference in free energy of thermal unfolding (change in Gibbs free energy) of the single and composite mutants relative to the wild type nitrile hydratase. The measured residual activity following thermal inactivation was used together with the Arrhenius equation and a three parameter non-linear fit to determine the free energy of thermal unfolding. The change in Gibbs free energy resulting from each thermostabilising mechanism coupled to the analysis of their crystal structures was used to suggest the contributing mechanisms. This study found that intersubunit interactions through hydrogen bonds and salt bridges are especially important for contributing towards thermal stability of tetrameric nitrile hydratases. Hydrophobic interaction through the formation of a water shell around hydrophobic side-chains and packing of hydrophobic side-chains was also observed to contribute to thermal stability. These results suggest a path towards rational design and engineering of thermostabilising mutations into nitrile hydratases. Increased thermostability would improve their large scale application in industry by allowing these enzymes to be more active for longer at higher temperatures and decrease the cost of amide production.